Are some brightly coloured European wild birds toxic? - Loxdale, Hugh D. (Frontiers in Ecology and Evolution, 2023)
Some colourful European wild birds display contrasting bright colours. These are often striking black and white or primary and secondary colours, and with the same basic plumage livery shared by both sexes. These contrasting colours are, one assumes, very obvious to predators when these birds forage diurnally, or continue other aspects of their life history, including courting, nest building and rearing their brood. Here, I posit that such birds may be displaying aposematic warning colouration, possibly enhanced by chemical noxious substances in their flesh and/or feathers, as is already known in certain bird species, including colourful as well as cryptic species. The warning colouration may be Müllerian or Batesian in nature, or maybe is a ruse to suggest to predators that they are in some way noxious, and thus to be avoided. Even if not actually noxious as such, this may give the intended prey time to escape. Certainly, birds like the very obviously blue-black and white patterned Eurasian magpie, Pica pica, are largely avoided by the Eurasian sparrowhawk, Accipiter nisus, although this of course could be a size-related avoidance, as other larger raptorial birds do predate it. These various possibilities are discussed in the present article.